Gastric Cancer Susceptibility according to Methylenetetrahydrofolate Reductase and Thymidylate Synthase Gene Polymorphism - Hun Jung; Jae Im Lee; Han Heong Lee; Soo Hong Kim; Hoon Hur; Hae Myung Jeon (Annals of surgical treatment and research, 2010)
Purpose: The genetic polymorphism and intracellular activity of methylenetetrahydrofolate reductase (MTHFR) and thymidylate synthase (TS) is clinically associated with carcinogenesis and biological therapeutic effect in gastrointestinal malignancies. We aimed to elucidate the susceptibility of gastric cancer according to MTHFR and TS gene polymorphism.Methods: This study was designed as a hospital-based case-control study in a single institute. The gastric cancer group (n=300) for the study was diagnosed at first time as tubular adenocarcinoma, and the control group (n=100) was diagnosed as no malignancy in the endoscopic biopsy. The genetic polymorphism of TS and MTHFR were confirmed by PCR.Results: The MTHFR mutant type had a more than 2-fold increased risk of developing gastric cancer (RR: 2.341). But, only heterozygote type (677CT) revealed significantly higher susceptibility compared to wild type (RR: 2.581). In TS gene genotype, the mutant genotype rate (2R/3R and 3R/3R) was significantly higher in gastric cancer group compared to control group (P=0.008), and the mutant type had a more than 3-fold increased risk of developing gastric cancer (RR: 3.222). In combined MTHFR and TS, 677CT＋2R/3R and 677CT＋3R/3R there was more than a 3-fold increased risk rate of developing gastric cancer compared with other combinations (RR, 3.474 in 677CT with 2R/3R; RR, 3.895 in 677CT with 3R/3R).Conclusion: This study shows a significant association between the MTHFR and TS polymorphisms and susceptibility to gastric cancer, providing a genetic basis. The polymorphisms study of two genes could be applied as susceptibility markers, clinically, for gastric cancer. Purpose: The genetic polymorphism and intracellular activity of methylenetetrahydrofolate reductase (MTHFR) and thymidylate synthase (TS) is clinically associated with carcinogenesis and biological therapeutic effect in gastrointestinal malignancies. We aimed to elucidate the susceptibility of gastric cancer according to MTHFR and TS gene polymorphism.Methods: This study was designed as a hospital-based case-control study in a single institute. The gastric cancer group (n=300) for the study was diagnosed at first time as tubular adenocarcinoma, and the control group (n=100) was diagnosed as no malignancy in the endoscopic biopsy. The genetic polymorphism of TS and MTHFR were confirmed by PCR.Results: The MTHFR mutant type had a more than 2-fold increased risk of developing gastric cancer (RR: 2.341). But, only heterozygote type (677CT) revealed significantly higher susceptibility compared to wild type (RR: 2.581). In TS gene genotype, the mutant genotype rate (2R/3R and 3R/3R) was significantly higher in gastric cancer group compared to control group (P=0.008), and the mutant type had a more than 3-fold increased risk of developing gastric cancer (RR: 3.222). In combined MTHFR and TS, 677CT＋2R/3R and 677CT＋3R/3R there was more than a 3-fold increased risk rate of developing gastric cancer compared with other combinations (RR, 3.474 in 677CT with 2R/3R; RR, 3.895 in 677CT with 3R/3R).Conclusion: This study shows a significant association between the MTHFR and TS polymorphisms and susceptibility to gastric cancer, providing a genetic basis. The polymorphisms study of two genes could be applied as susceptibility markers, clinically, for gastric cancer. KCI Citation Count: 4